Linear Operator and Spontaneous Breaking in PT -Symmetry - Mohapatra, Prachiprava (JOURNAL OF ADVANCES IN PHYSICS, 2018)
We study spectral behaviour of linear operator using matrix diagonalisation method and notice that spectral breaking is an inherent behaviour in PT -symmetry .